The cotton aphid, Aphis gossypii Glover and predators on Catalpa bignonioides Walt. - Lea MILEVOJ (Acta Agriculturae Slovenica)
In 1998–2001, the cotton aphid (Aphis gossypii Glover, Homoptera, Aphididae) was found to complete its holocycle on Catalpa bignonioides Walt. in Ljubljana (Slovenia). The infested leaves showed curling. The aphid was very damaging by causing the flowers to abort. Many natural enemies (Adalia bipunctata, Chrysoperla carnea, Aphidoletes aphidimyza, Scymnus and Orius species) attack A. gossypii very succcesfully.